Movement assessment battery for children-second edition (MABC2): Cross-cultural validity, content validity, and interrater reliability in Thai children - Rujira Jaikaew (2020)
Copyright © 2019 Rujira Jaikaew and Nuntanee Satiansukpong. Introduction. The Movement Assessment Battery for Children-Second Edition (MABC2) is a standardized test for detecting children with movement difficulty. It was established and is used widely in Western countries. Studying cross-cultural validity and reliability was necessary before using the MABC2 with Thai children. Purposes. To study cross-cultural validity, content validity, and interrater reliability of the MABC2. Method. The MABC2-Age Band 2 (AB2: children aged 7-10 years) was translated into Thai from the source version of the MABC2 by using the following steps: forward translation, backward translation, panel discussion, and testing of the prefinal version of the Thai-MABC2-AB2. Five occupational therapists checked the content validity of the test. Twenty-nine children, aged 7-10 years, were examined by two testers in order to establish interrater reliability. Results. This cross-cultural study demonstrated validity in the Thai context. Content validity was good with an item-objective congruence (IOC) range from 0.73 to 0.95. The intraclass correlation coefficient (ICC) of interrater reliability ranged from 0.71 to 1.00. Conclusion. The Thai-MABC2-AB2 is a good fit for use in a clinical and Thai cultural setting. Interrater reliability was moderate to good, which meant results between testers were consistent.